KONFLIK BATIN TOKOH KIM JI-YEONG DALAM NOVEL KIM JI-YEONG LAHIR TAHUN 1982 KARYA CHO NAM- JOO - Agusman; Iswadi Bahardur; Ricci Gemarni Tatalia (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to analyze and describe the various forms of inner conflict experienced by the main character, Kim Ji-yeong, in the novel "Kim Ji-yeong Born in 1982" by Cho Nam-joo. This novel is highly relevant because it depicts the complex experiences of Korean women in facing patriarchal social pressures and expectations. Through the analysis of inner conflict, this study shows that women have complex desires, aspirations, and struggles in life, and they are not passive creatures. The type of research used is qualitative with a descriptive approach. The research data were taken from words or sentences contained in the novel itself. Data analysis was carried out through the stages of data collection, data analysis, and drawing conclusions. The results of the study revealed five forms of inner conflict found in the character of Kim Ji-yeong. First, a painful neurotic inner conflict, characterized by perfectionism, self-blame, and pressure from family. Second, inner conflict moves toward others, where Ji-yeong tries to conform to social expectations to avoid conflict. Third, inner conflict moves against others, shown by Ji-yeong's efforts to aggressively fight against her family. Fourth, the inner conflict of moving away from others, which makes Ji-yeong feel isolated, inferior, and lose her identity due to constant pressure. Fifth, the inner conflict of an unrealistic ideal image, where Ji-yeong is expected to be a perfect mother, wife, and worker without adequate support. Overall, this study not only provides an in-depth understanding of the experiences of fictional characters but also provides insights into the social realities faced by many women worldwide, including in Indonesia. Keywords: Inner Conflict, Kim Ji-yeong, Literary Psychology, Novel, Gender